The legal validity of the judicial judgment issued on the basis of potential interest ( A comparative study ) - Abd Aleali Matlak , Dhikraa; Abdul-Ali Khashan , Prof.Dr.Ali (Basra studies journal, 2022)
The resort to justice to obtain judicial protection for legal centers or the right aperson threatened with assault is truly one of the most important rights stipulated by constitutions ,and in order to prevents the eternity of disputes, instability of legal centers and possible judicial rulings . contradictory, which lead to peoples distrust and respect for the judicial work and wastes prestige judiciary therefore, a judicial ruling based on a potential interest must be for this the ruling the authoritative of the resent order in which according to this argument is that the judicial ruling based on the potential interest the donor of judicial protection with its decisive chapter in the dispute as soon as it is issued and this judgment is the title of the truth the adjudgement of the res judicata proves judicial protection under the law and is important a process with its effects that the previously adjudicated case may not be revisited . The court ruling becomes an unprovable legal frencing , this argument it is relative between the adversaries themselves and cannot be invoked against others who were not a party in the lawsuit .